Flowering phenology, nectary structure and breeding system in Corymborkis flava (Spiranthoideae : Tropidieae), a terrestrial orchid from a Neotropical forest - Vieira, Milene Faria; Andrade, Maria Regina S.; Bittencourt, Nelson S.; de Carvalho-Okano, Rita M. (CSIRO Publishing, 2007)
Flowering phenology, breeding system and nectary structure of Corymborkis flava (Sw.) Kuntze were studied in a fragment of the Atlantic Forest in south-eastern Brazil. The flowering period extended from March (end of rainy season) to early June and seed dispersal occurred from June to September (dry season). Flowering peak occurred mainly in April, with up to 34 open flowers per plant being observed. The yellow, odourless and tubular flowers lasted similar to 7.8 days. The flowers present a perigonal nectary located in the basal lateral parts of the labellum; this is the first report on the nectary location and characterisation in the Tropidieae tribe. At the pre-anthesis stage, cells of both secretory parenchyma and epidermis of the nectary are filled with compound amyloplasts. However, starch grains were not observed in these tissues in senescent flowers, indicating that these starch grains are hydrolysed and used as source of sugars for nectar production. The nectar accumulates between the cuticle and the outer periclinal wall of the epidermal cells before. owing out into the nectar chamber. C. flava is a self-compatible species and spontaneous self-pollination does not occur because of hercogamy. The high pollinia removal (0.80) and insertion (0.82) per flower, as well as the high natural fruit-set indicate an efficient natural pollination system. The present study contributes for the knowledge of the diversity of reproductive strategies and nectary structures in Orchidaceae.